Vibrational spectroscopic studies of three dimensional host lattices formed by pyrazine bridges between tetracyanonickelate layers - Davies, J. Eric D.; AKYÜZ, SEVİM; AKYÜZ, ZEKİ TANIL (Kluwer Academic Publishers, 1990)
Three dimensional host lattices have been developed by forming bridges with bidentate pyrazine molecules between adjacent tetracyanonickelate polymeric layers of Ni(II) or Cd(II). The Fourier-transform IR and Raman spectra (4000-200 cm−1) of the compounds with the general formula M(pyz)Ni(CN)4, (where M = Ni or Cd) are reported. These host lattices can include benzene molecules but it is found that aniline molecules cannot be included in these structures. They, however, form complexes with the formula M(an)2Ni(CN)4, by replacing pyrazine ligands. A monodentate pyrazine complex of Cd(II) with the formula Cd(pyz)2Ni(CN)4 has also been prepared.
Keywords: Tetracyanonickelate compounds; benzene clathrate; pyrazine complexes; IR and Raman spectra